The role of ICT in a globalised knowledge production - Shamsul A.B.; Rumaizah Mohamed; Haslindawati Hamzah (Universiti Kebangsaan Malaysia, 2004)
This essay intends to explore and describe the relationship between knowledge production and globalization mediated through information and communication technology (ICT). The first part deals with the current trend and development in knowledge production around the world by examining how globalisation has affected patterns of knowledge production in three key aspects of knowledge system, namely, epistemology, ontology and methodology. The second part of the essay examines the nature of contradictions generated by the presence of ICT and globalization in knowledge production such as the ‘dividedness’ that has been generated by the existence of “nation-states”. The experience of the Southeast Asian region is presented as a case study. The final part of the essay touches on the issue of access and equity as well as democratization of knowledge in the context of ICT, globalization and knowledge production